XRF-Escape Scintillator Footprints for Nuclear Medicine Imaging and Gamma-Ray Spectrometry - Raffaele Scafè; Marco Puccini; Rosanna Pellegrini; Roberto Pani (Photonics)
The present paper introduces the so-called scintillator footprints, consisting of plots showing XRF-escape peaks and their relative emission intensities in the energy range of interest for nuclear medicine SPECT and PET. A footprint describes the suitability of a scintillator for quantitative investigation with the best possible detectability. Sixteen scintillation materials have been identified in the literature, characterized by effective atomic numbers Zeff ranging between 22 and 75. The footprints of NaI:Tl and BGO, confirm the best suitability for quantitative spectral analysis in SPECT and PET, at 140.5 keV and 511 keV, respectively. Moreover, for the low-Zeff scintillators like CaF2 and CMSM, the XRF-escape effect is to predict irrelevant even at 140.5 keV due to the small energy value of X-ray fluorescence.